Comparison of triglyceride glucose index and other insulin resistance indexes in children with overweight and obesity - Derya Kalyoncu; Melis Kavrak Kursun (BMC Endocrine Disorders)
Abstract Objectives The aim of the study was to determine the correlation between insulin resistance (IR) indexes in children with overweight or obesity. Methods A total of 276 children with overweight or obesity and 100 normal-weight children were enrolled in the study. IR indexes such as homeostasis model assessment insulin resistance (HOMA-IR), quantitative insulin-sensitivity check index (QUICKI), fasting glucose/insulin ratio (FGIR), Triglyceride glucose index (TyG), and lipid-derived ratios were determined. Results The mean ages were 13.0 ± 2.6, 13.1 ± 2.7 and 12.72 ± 2.23 (range:6 - 18 years) for children with overweight, obesity and normal-weight, respectively. A statistically significant positive correlation was found between HOMA-IR and TyG index, and a negative correlation between QUICKI, FGIR and TyG index (r = 0.193, P < 0.001; r = - 0.456, P < 0.001 and r = - 0.392, P < 0.001, respevtively). TyG index, triglyceride (TG)/high-density lipoprotein (HDL), total cholesterol (TC)/HDL, and low-density lipoprotein (LDL)/HDL were higher in children with IR than those without IR (P < 0.05). In receiver operating characteristic curves analysis, cut-off points were found to be ≤ 0.31 for QUICKI (94.31% sensitivity and 97.58% specificity), ≤ 6.3 for FGIR (89.1% sensitivity and 93.94% specificity), and > 4.62 for TyG (49.29% sensitivity and 84.85% specificity). Conclusion HOMA-IR, FGIR, and QUICKI constitute stronger predictors of IR than TyG index in children with overweight and obesity.